2010
DOI: 10.1523/jneurosci.2968-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

State-Dependent Firing Determines Intrinsic Dendritic Ca2+Signaling in Thalamocortical Neurons

Abstract: Activity-dependent dendriticsignaling properties that are spatially and temporally modified in a behavioral state-dependent manner and suggest that backpropagating action potentials faithfully inform proximal sensory but not distal corticothalamic synapses of neuronal output, whereas corticothalamic synapses only "detect" Ca 2ϩ signals associated with low-threshold spikes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 45 publications
6
65
2
Order By: Relevance
“…When considered alongside our own previous studies (Errington et al, 2010, 2012; Connelly et al, 2015, 2016) and those of others (Crandall et al, 2010, Cueni et al, 2008, Chausson et al, 2013), these new findings allow us to build a more complete picture of the role that dendrites play in thalamic neuron electrogenesis and signaling.…”
Section: Discussionmentioning
confidence: 60%
“…When considered alongside our own previous studies (Errington et al, 2010, 2012; Connelly et al, 2015, 2016) and those of others (Crandall et al, 2010, Cueni et al, 2008, Chausson et al, 2013), these new findings allow us to build a more complete picture of the role that dendrites play in thalamic neuron electrogenesis and signaling.…”
Section: Discussionmentioning
confidence: 60%
“…The robustness of RD could partly be attributed to the high density of expression of T-type Ca 2? channels in the soma and dendrites of thalamic relay neurons [37][38][39]. Third, RD can be recorded in most MGB neurons in young animals (P15-22).…”
Section: Rd In Mgb Neurons Is Carried By T-type Ca 21 Channelsmentioning
confidence: 95%
“…Baseline levels of [Ca 2+ ] ranged from 50–80 nM in parafascicular thalamic neurons using bis-fura 2 [14]. Dendrites can actively sustain low frequency activity in thalamocortical neurons [911]. These authors showed dendritic [Ca 2+ ] dynamics (using fluorescence recordings of fluo-filled thalamocortical neurons) during repetitive low frequency spikes [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Dendrites can actively sustain low frequency activity in thalamocortical neurons [911]. These authors showed dendritic [Ca 2+ ] dynamics (using fluorescence recordings of fluo-filled thalamocortical neurons) during repetitive low frequency spikes [10,11]. Morever, ryanodine receptor-dependent Ca 2+ -induced Ca 2+ release [11,34], and Ca 2+ -dependent K + channel activation [42], might blunt the amplitude of [Ca 2+ ] mediated fluorescence signals.…”
Section: Discussionmentioning
confidence: 99%